New Applications of “Abeer-AL-Tememe” Transformation in partial differential equations - F. Abaas, Abeer; H. Mohammed , Ali (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2024)
The Introduction of integral transforms as a partial differential equation solution technique results from the tremendous significance of differential equations and integral transforms in scientific domains. This study proposes a new integral transform Abeer Al- Tememe transform. The suggested transform applications has demonstrated its capacity to resolve partial differential equations.